(untitled) (Proceedings of International Conference on Special Education, 2022)
Autism has become the fastest growing category of special education since it was added to the Individuals with Education Act (IDEA) in 1990. The numbers of Autism have continued to grow almost exponentially. The increase in the number of children ASD and the range of abilities among those children has brought a question and concerns on how to provide an appropriate public education in the least restrictive environment to the children on the spectrum. The increasing of ASD children were not followed by the numbers of special schools that far from formal schools. This condition triggering the ASD parents and formal school to start sending and excepting the ASD children in formal schools. With the limited understanding about inclusive education, the formal schools tend to claim full inclusion program in their school only from the present of the ASD students in their formal classes. The formal schools only adapt the condition with the general education system without obtaining the inclusion program. The system from general education may not appropriate with the condition for ASD students. After years the result from the ASD children become variety that lead to improvement or degradation. With uncertainly result school need to look back their condition to give better future for the ASD students.